Study on Navigation Conditions and Shipping Traffic on the Danube in the Period 2001-2020: Array - Chirosca, Ana Maria; Rusu, Liliana (Journal of Danubian Studies and Research, 2021)
The Danube, the second largest river in Europe after the Volga and the third largest in terms of economic importance after the Volga and Rhine, is 2 840 km long and crosses a total of 4 capitals and 10 countries. With a long history in commercial transport, the Danube is connected to the Black Sea by the Danube-Black Sea canal and to the North Sea by the Rhine-Main-Danube Canal. The economic importance of this river stems from its large shipping capacity at a much lower cost than other types of transport. At the same time, the Danube has a tourist importance due to the Danube Delta, one of the most beautiful regions in Romania due to the fauna and flora found in this area. In this paper, a statistical analysis was carried out on the naval traffic for the period 2001-2020 regarding the total number of incoming ships, outgoing ships and the total tons of cargo transported on the Sulina canal. The most important sectors and ports were identified, and a classification of the types of goods according to their contribution was made.